Low caffeine dose improves intermittent sprint performance in hot and humid environments - Nakamura, D.; Tanabe, Y.; Arimitsu, T.; Hasegawa, H.; Takahashi, H. (Journal of Thermal Biology, 2020)
While the effects of caffeine have been evaluated in relation to endurance exercise, few studies have assessed the ergogenic effects of low caffeine doses on intermittent exercise performance in hot and humid environments. Thus, we aimed to determine the effects of low-dose caffeine supplementation on intermittent exercise performance under these conditions. Eight male soccer players (age, 19.9 ± 0.3 years; height, 173.7 ± 6.3 cm; body mass, 65.1 ± 5.5 kg; VO2max, 50.0 ± 3.1 mL kg-1 min-1) participated in this double-blind, randomized, cross-over study. Caffeine was orally administered at 60 min before exercise (dosage, 3 mg kg-1). The participants completed a 90-min intermittent sprint cycling protocol under two conditions (after receiving caffeine and placebo) at 32 °C and at 70% relative humidity. A significant improvement in the total amount of work was observed in the caffeine condition compared to the placebo condition (155.0 ± 15.8 vs 150.8 ± 14.5 kJ, respectively; p < 0.05, d = 0.28). In contrast, the rectal temperature measured at the end of exercise showed no significant difference between the conditions (38.9 ± 0.4 °C and 38.7 ± 0.5 °C in the caffeine and placebo conditions, respectively; p > 0.05, d = 0.57). Other thermal responses, such as the mean skin temperature, heart rate, or sweat volume, were not significantly different between these conditions. These results suggested that a low caffeine dose improved the intermittent sprint performance and the reasons could be explained by the fact that a low caffeine dose ingestion did not affect the thermoregulatory responses compared to the placebo condition and, thus, did not attenuate its ergogenic effect on exercise in hot and humid environments.